Wayground Paper Mode: An Innovation of Game Based Learning Evaluation Tools in Islamic Elementary Schools - Elfiana, Dwi Endah; Mufida, Shobrina Nurul; Sari, Dyah Permata; Susilawati; Nuraini, Melan; Solikha, Sella Rizkiyatus (Proceeding International Conference on Education, 2025)
Learning evaluation in Islamic elementary schools often relies on conventional methods that are less engaging and do not fully encourage active student participation. Although several technology-based innovations have been introduced, they often require digital devices that are not always available in every school, which limits their use. Therefore, this study aims to develop Wayground Paper Mode as an innovative game-based learning evaluation tool for use in madrasah ibtidaiyah (Islamic elementary schools). The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) as a research and development methods. The product was tested with 24 students aged 10–11 years (8 male and 16 female) at MI Plus Al-Fatimah Bojonegoro on the material of energy changes. The validation process involved analyzing test items and assessing media feasibility through the Facet Rasch Model to obtain objective data from expert judgment. In addition, student responses to the media were collected through questionnaires. The results show that Wayground Paper Mode has a high level of validity and received positive feedback from students. This innovation demonstrates that a game-based evaluation approach can create a more interactive, enjoyable, and meaningful learning experience in Islamic elementary school settings.